PETANI KARET DI NAGARI GUNUANG MALINTANG TAHUN 1998-2020 - Dinda Sri Vidya; Etmi Hardi (Ensiklopedia of Journal, 2023)
Abstract: Nagari Gunuang Malintang is one of the rubber producing areas in 50 Kota District. The majority of the Gunuang Malintang people work as rubber farmers, with the presence of rubber farmers in Gunuang Malintang Nagari, some of the people work as rubber farmers in Gunuang Malintang Nagari. The purpose of this research is to find out how rubber farmers are dealing with the economic conditions of rubber farmers in Nagari Gunuang Malintang in 1998-2020. The method used in this study is the historical method, namely: heuristics, source criticism, interpretation, and historiography. the research results found can be seen from the presence of rubber farmers in Nagari Gunuang Malintang. The sale of rubber in Nagari Gunuang Malintang by farmers was only done once, namely on Thursday. With the existence of a rubber plantation in Nagari Gunuang Malintang, it can open jobs for the people in Nagari Gunuang Malintang.Keyword: Farmer, Rubber, Mount Malintang